Integrated model for energy consumption information of complex building based on BIM technology. (2nd August 2021) - Chen, Xia; Miao, Lin
In order to solve the problem of poor accuracy of energy consumption test in traditional complex building energy consumption information synthesis model, a BIM-based complex building energy consumption information synthesis model is proposed. The dynamic visual programming method is used to set and select the parameters of the complex building's peripheral structure. According to the network terminal, the basic data of energy consumption of the comprehensive architecture are obtained. The basic data of cloud computing are simulated, quantitative research and regression analysis are carried out. BIM technology is used to complete the construction of comprehensive model of energy expenditure information for complex buildings. The experimental results show that the root mean square error of the model is small, only 2.5%. The variation range of the measured coefficients is 0.6-0.8, which shows that the model has high test accuracy.